Recruitment: It's challenging - White, K.; Waters, Rebecca; Buchanan, Angus (Wiley-Blackwell, 2018)
Background: Difficulties in recruiting people with intellectual disability to actively participate in research is a recurring topic of discussion that has been minimally investigated. Capturing this issue and its depth is essential to involving people with intellectual disability in research. Method: Semi- structured interviews were utilised to obtain perspectives of recruitment from 12 academic researchers with substantial experience in the field. Data were analysed using Straussian grounded theory. Results: The core category was ‘Recruitment: It ’ s challenging’, informed by seven categories; differentiation of people with intellectual disability as a research population, lived experience of researchers, gatekeeping, ethical considerations, research design, collaboration, and rapport. Conclusions: Researchers developed and employed strategies over time and experience in response to recruitment challenges. These strategies largely focused upon creating, strengthening and supporting a connection between themselves and people with intellectual disability. There is potential for future investigation and further development of strategies to improve recruitment.